Pengaruh Model Self-Directed Learning (SDL) Terhadap Kemampuan Menulis Teks Eksplanasi Kompleks Pada Siswa Kelas XI SMA Swasta Abdi Negara Binjai - Simanungkalit, Atri Novela; S, Monalisa Frince; Sitohang, Tigor (Lembaga Riset dan Inovasi Almatani, 2024)
The purpose of this study is to determine the influence of the use of the Self-Directed Learning (SDL) learning model on the ability to write complex explanation texts in Grade XI students of Abdi Negara Private High School Binjai Academic Year 2023/2024. This research is quantitative with an experimental research method, using a One Group Pretest and Posttest research design. The research population is 82 and the sample is 30 people. Sampling was done using Cluster Sampling technique. The results of the pretest show that the number of students who passed the Minimum Completion Criteria (KKM) in writing complex explanation texts is 6 people (20%). and after using the learning model, there is an increase in the number of students who achieve the learning completeness standard by 23 (76%) people. Obtained 1-calculation 5.58 and Label 1.70 then Ho rejected and H1 accepted. It is concluded that the use of the Self-Directed Learning (SDL) learning model can improve students' news writing abilities in Indonesian language lessons at the Grade XI level of high school.